Analysis of Hole Lifetime in SOI MOSFET Single-Photon Detector - Putranto, Dedy Septono Catur; Du, Wei; Satoh, Hiroaki; Ono, Atsushi; Priambodo, Purnomo Sidi; Hartanto, Djoko; Inokawa, Hiroshi (UI Scholars Hub, 2013)
Hole lifetime in the silicon-on-insulator (SOI) metal-oxide-semiconductor field-effect transistor (MOSFET) singlephoton detector was evaluated by the analysis of drain current histograms for different light intensities and substrate voltages. It was found that the peaks in the histogram corresponding to the larger number of stored holes grew as the gate bias decreased. This was attributed not to the increased light absorption efficiency or collection efficiency of the photo-generated holes, but to the prolonged hole lifetime presumably caused by the higher transverse electric field inside the body of SOI MOSFET.